Post-infectional phenolic changes in maize due to Rhizoctonia solani f. sp. sasakii causing banded leaf and sheath blight - AKHTAR*, JAMEEL; JHA, VINAY KUMAR; LAL, HEM CHANDRA (Indian Phytopathology, 2011)
A basic study was undertaken to find out the possible role of the phenolics involved in resistance against bandedleaf and sheath blight of maize. The phenolic content in all cultivars of maize increased after infection. This increase was moreÂ pronounced in resistant cultivars as compared to susceptible cultivars. The highest increase (32.14%) in accumulation ofphenolics was noticed in diseased leaves of genotype BVM-4 infected with the Rf isolate. Accumulation of total phenol indiseased leaves of 10 genotypes against 5 isolates of R. solani varied from 119.67 to 160.33 Î¼g/g fresh weight and in healthyleaves 111.66-124.33 Î¼g/g fresh weight. Further analysis of the data revealed that the disease severity was negatively correlatedwith the accumulation of phenol having coefficient of correlation r = -0.83.